Influência dos processos físicos e sinóticos nas trajetórias dos complexos convectivos de mesoescala no nordeste brasileiro entre 2008 e 2015 - Lyra , Matheus José Arruda (2018)
Short-term weather forecast of the mesoscale systems is relevant for the operational studies and useful for the whole population due to the forecast of the various types of associated adverse phenomena. The main purpose of this study was the analyses of the different processes that influenced the trajectories during the development of the Mesoscale Convective Complexes (MCC) in the Brazilian Northeast (BNE) in 2008 – 2015. METEOSAT satellites images in the Infrared (IR) and Water vapor (WV) channels were used for the events identification. Maddox (1980) standards were used for the cases selection using the automatic analysis algorithm of GNU Octave software. National Center for Environmental Prediction (NCEP) reanalysis data II were used together with the OpenGrADS software for the meteorological fields construction. Daily precipitation were consulted through the automatic and conventional stations of the Meteorological Data for the Education and Studies (BDMEP) from the National Institute of Meteorology network (INMET) stations. Fifty-seven MCC cases have been analyzed in the study region, where more than 80% of them started the development between 00 - 03 UTC. The average coverage area of these MCC was 120,000 km², with the highest occurrences mainly between 50,000 and 150,000 km². Among the main BNE’s synoptic systems were identified Upper Tropospheric Cyclonic Vortex (UTCV), Intertropical Convergence Zone (ITCZ), Frontal Extremity, Wave disturbance in trade winds, Cyclonic Circulation Center and Trade winds were identified as the principal factors that boosted events formation. MCC trajectories varied according to the synoptic systems related to their formation and relief of the BNE area where they developed. MCC developing in latitudes near the equator were correlated to the ITCZ, with the displacement parallel to streamlines directions at the low levels, predominant to West. The cases developed closer to Bahia state had greater influence of the local topography, with the high acting on the Ocean and near the coast. Thus, one could emphasize the importance of these results for the forecasting of these systems in the region because of its complexity and the extensive area that covers the NEB.